Intercultural scale of conceptions of disability: Constructions and psychometric studies - Leite, Lúcia Pereira [UNESP]; Cardoso, Hugo Ferrari [UNESP]; de OLIVEIRA, Taize [UNESP] (FapUNIFESP (SciELO), 2021)
The same instrument may be suitable for different realities, but in order to actually assess conceptions linked to a particular cultural context, it is necessary to understand the phenomenon under the lens of this scenario. The objective of this paper was to present preliminary results of validation and reliability of the Escala Intercultural de Concepções de Deficiência – EICD (Intercultural Scale of Conceptions of Disability) for the Brazilian reality. EICD is an instrument developed by a team from different countries (Brazil, Spain and Portugal) and aimed at assessing concepts of disability. Qualitative validation (based on content) was carried out, by means of national and international judges, and by verification of main components carried out by exploratory factor analysis of the data collected with a Brazilian sample group. The final version included translation and back-translation into four different languages: Spanish (Cuba), Catalan (Barcelona), Castilian (Seville) and Portuguese (Portugal). Regarding the factorial study for the Brazilian reality, the EICD was composed of 43 items, distributed in three dimensions (Biological Conception, Social Conception and Metaphysical (Religious) Conception). Future studies will be necessary for the psychometric improvement of the instrument, both in the national and international context.
Escala intercultural de concepções de deficiência: Construção e estudos psicométricos
Keywords: Conception; Disability; Internal consistency; Psychometric procedures; Scale